The Effectiveness of a Combination of Relaxation and Cognitive Restructuring Techniques in Managing Anxiety in College Students - Atensi, Mitra; Rifameutia, Tjut (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Anxiety disorders are one of the most common mental health problems experienced by adolescents and young adults around the world, including university students. Those who experience anxiety often face difficulties in learning and problem-solving. In the cognitive behavioral therapy approach, one of the most common sources of anxiety is irrational thoughts and beliefs within the individual. If left untreated, anxiety can lead to severe consequences, including depression. This study aims to assess the effectiveness of a combination of cognitive restructuring therapy and relaxation techniques in reducing anxiety and irrational thoughts that trigger anxiety in college students. The research method used a single-subject pre-test post-test design with the subject being a 22-year-old male college student. Measurements were taken using the Beck Anxiety Inventory (BAI) and the Shortened General Attitudes and Beliefs Scale (SGABS). The results showed the effectiveness of the intervention in reducing irrational attitudes and beliefs that trigger anxiety in the subject. Subjects became more proficient in identifying, debating, and restructuring irrational thoughts into rational and adaptive thoughts. In addition, the subjects effectively applied relaxation techniques, which helped them feel more comfortable when facing anxiety-provoking situations. The implications of this study indicate the importance of applying a combination of cognitive restructuring therapy and relaxation techniques in overcoming anxiety among college students.Gangguan kecemasan adalah salah satu gangguan mental yang paling umum terjadi pada remaja dan dewasa muda di seluruh dunia, tak terkecuali pada mahasiswa. Mahasiswa yang mengalami kecemasan dilaporkan menderita kesulitan belajar dan pemecahan masalah. Dalam pendekatan terapi perilaku kognitif, salah satu sumber kecemasan yang paling sering ditemui adalah pemikiran dan keyakinan yang irasional pada diri individu. Apabila tidak ditangani dengan tepat kecemasan dapat berakibat fatal dan berujung pada depresi. Penelitian ini bertujuan untuk mengkaji efektivitas kombinasi terapi restrukturisasi kognitif dan teknik relaksasi dalam mengurangi kecemasan dan pemikiran irasional yang memicu kecemasan pada mahasiswa. Metode penelitian yang digunakan adalah desain subjek tunggal pre-test post-test dengan satu mahasiswa laki-laki berusia 22 tahun sebagai subjek. Pengukuran dilakukan dengan menggunakan Beck Anxiety Inventory (BAI) dan Shortened General Attitude and Beliefs Scale (SGABS). Hasil penelitian menunjukkan bahwa intervensi ini efektif dalam menurunkan sikap dan kepercayaan irasional yang memicu kecemasan pada subjek. Subjek menjadi lebih mampu mengidentifikasi, mendebat, dan merestrukturisasi pemikiran irasional menjadi lebih rasional dan adaptif. Subjek juga dapat menerapkan teknik relaksasi dengan efektif yang membantu dirinya merasa lebih tenang dalam menghadapi situasi yang memicu kecemasan. Implikasi dari penelitian ini adalah pentingnya penerapan kombinasi terapi restrukturisasi kognitif dan teknik relaksasi dalam mengatasi kecemasan pada mahasiswa.